Measuring, Evaluating, and Mapping the Electromagnetic Field Levels in Turgut Ozal Medical Center Building and Environment (Annals of Medical Research, 2021)
None
Keywords: Electric and Magnetic Fields; High Frequency Electromangnetic Field; Electromagnetic Field Monitoring in Hospitals; Electromagnetic Pollution Maps.